Emotional intelligence and academic achievement among undergraduates in Kota Samarahan - Jesica, Bat (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study investigated the relationship between emotional intelligence and academic achievementa mong undergraduatesin Kota SamarahanT. his study also investigated the differences in undergraduate's emotional intelligence and academic achievement by demographic factors. Quantitative method was used to investigate this study. Schulte Emotional Intelligence Scale (SEIS) was tested on 101 samples to investigate relationship between emotional intelligence and academic achievement. Cumulative Grade Point Average (CGPA) was used to measured academic achievement. Pearson Correlation test was used to test relationship between emotional intelligence and academic achievement. Independent T- Test was used to examine the difference in emotional intelligence and academic achievement by gender among undergraduates. One Way ANOVA was used to investigate the difference in emotional intelligence and academic achievement by ethnic among undergraduates generally, the research findings indicated a significant relationship between emotional intelligence and academic achievement. No differences were found between emotional intelligence and academic achievement by gender and ethnic. This study suggests emotional intelligence to be emphasized in education program development to further improve academic achievement.